La pratique de la parenté : politique factionnelle, redoublement et réitération d’alliance chez les Katukina (Brésil) - Jérémy Deturche (Journal de la Société des Américanistes)
This article is an analysis of what I call the practice of kinship among the Katukina of the rio Biá (Brazilian Amazon). It is an attempt to understand, from a statistical interpretation of marriages from a genealogical corpus collected between 2004 and 2009, the dynamics of the policy of katukina marriage alliances. Thus, I hope to show how the Katukina relate their matrimonial choices to kinship relationships. Understanding factional politics then becomes necessary to explain the patterns of marriages and helps to perceive how kinship nomenclature is “practiced” in the political dynamics that underlie the compositions of local Katukina groups. The fluidity that characterizes the katukina system becomes an intrinsic component of the policy of kinship that they practice, anchored in the importance of the married couple and in the reiterations-replications of alliances.